Culpabilidad sin posibilidad de obrar en contrario: ¿una necesaria revisión de la ubicación de la (in)imputabilidad? - Díaz Arana, Andrés Felipe (Derecho penal y criminología, 2023)
This article briefly reviews the problem of the possibility of acting otherwise as an element of culpability. It also proposes a compatible interpretation of the concept of freedom with both determinism and criminal responsibility. Finally, it applies the considerations exposed to determine the nature of the apology and the systematic location of the non-imputability in the material theory of crime.